Z-plasty in axillary retraction: techniques and strategies to facilitate learning by medical residents - Mariana Alcantara Rodrigues de Moraes; Roberto Rudge Ramos; Lydia Masako Ferreira (Revista Brasileira de Cirurgia Plástica, 2017)
INTRODUCTION: Herein, we present two cases of post-burn retraction of the axillary region, which were subsequently surgically corrected using multiple Z-plasties. We present a marking strategy to facilitate the learning of this procedure by plastic surgery residents. METHODS: Two patients with axillary and upper limb retractions due to burns with hot liquids were surgically treated using multiple Z-plasties. The strategy proposed in this study recommends the marking of the triangular flap located at the midpoint of the axillary retraction, which then advances and crosses the axis of the scar. Then, subsequent flaps are made at an angle of 60º to each other. We believe that this systematization of marking facilitates the planning and learning of Z-plasty. RESULTS: The study patients achieved an adequate range of motion and functional recovery of the affected limb postoperatively. We observed no cases of necrosis of the flap ends, which should be carefully worked and slightly rounded. The execution of the procedure was simple using the suggested marking strategy. CONCLUSION: The presented marking strategy was reproducible and easy to learn. Multiple Z-plasties were effective in restoring the range of motion of the areas affected by burns that were treated using this method.